ANALISIS KESUKSESAN PRODUK MINUMAN SUPLEMEN (THE ANALYSIS OF SUCCESSFUL BEVERAGE SUPLEMENT PRODUCT) - , Mathilda Sri Lestari, Ir. Subagyo, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to know the success beverages supplement products and the characteristics causing their success. The beverages supplement used as the research objects are: Kratingdaeng, Kratingdaeng-S, M-150, Hemaviton Energy Drink, Hemaviton Jreng, Lipovitan Ginseng, Lipovitan Honey, Lipovitan Pasak Bumi, Kuku Bima, Kuku Bima Ener-G, Panther, Extra Joss. The success indicators used are the combination between the market share and repeat order rate. The characteristics causing the success which are analyzed such as the factor: packaging aesthetic, taste, function, main ingredients, additive ingredients, the inside packaging instruction, taste variants, price and the launching year product. To chose the products which are success according to market share, this research use the pareto diagram and for the success products according to repeat order rate use questioner. Kuku Bima Ener-G, Extra Joss, Hemaviton Jreng and Kratingdaeng are as the success products analyzed by strategy canvas and correlation test. From the result of the research, the result shows that Kuku Bima Ener- G is the most successful beverages supplement according to the combination of indicators of market share and repeat order rate with the total score is 51,97. The factors: additive ingredient, taste variants, price and the launching year product are the causal factors causing Kuku Bima Ener-G is success. The advance researches about the other causing factors are needed to be done.